FORMULASI SALEP ANTIBAKTERI EKSTRAK ETANOL DAUN TEMBELEKAN (LANTANA CAMARA L) - Parwanto, ML Edy; Senjaya, Hardy; Edy, Hosea Jaya (PHARMACON, 2013)
Tembelekan (Lantana camara L) is a wild plant that its leaves contain chemicals such asphenols, flavonoids and alkaloids. Chemical constituents in tembelekan allegedly hasantibacterial ability against Staphylococcus epidermidis. This research aims to create anantibacterial ointment to the active substance ethanol extract of leaves tembelekan.Antibacterial ointment tembelekan ethanol extract of the leaves made in two concentrations,namely 20% and 24%. Conducted quality testing ointment is organoleptic test, homogeneitytest, test and test pH value dispersive power. Quality test results conducted on theconcentration ointment with two parameters meet the organoleptic test, test and test pH valuehomogeneity. Tembelekan leaf extract ointment ethanol concentration of 20% and 24% didnot meet the quality parameters to test dispersive power.Keywords: Ethanol Leaf Extract tembelekan, ointments, test quality.